2020
DOI: 10.3389/fnins.2020.00100
|View full text |Cite
|
Sign up to set email alerts
|

Power Modulations of ECoG Alpha/Beta and Gamma Bands Correlate With Time-Derivative of Force During Hand Grasp

Abstract: It is well-known that motor cortical oscillatory components are modulated in their amplitude during voluntary and imagined movements. These patterns have been used to develop brain-machine interfaces (BMI) which focused mostly on movement kinematics. In contrast, there have been only a few studies on the relation between brain oscillatory activity and the control of force, in particular, grasping force, which is of primary importance for common daily activities. In this study, we recorded intraoperative high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 67 publications
3
23
0
Order By: Relevance
“…Additionally, they are also consistent with numerous studies suggesting a negative relationship between low-frequency power, including the alpha band, and high-frequency power, including BHA, during sensory, motor and task processing. Specifically, increased high-frequency power co-occured with decreased low-frequency power after the presentation of visual (Lachaux et al, 2005;Martin et al, 2019;Nir et al, 2007Nir et al, , 2017Rodriguez et al, 2004;Fisch et al, 2009;Miller et al, 2014;Podvalny et al, 2015;Fries et al, 2001;Scheeringa et al, 2011;Hwang & Andersen, 2011;Rickert et al, 2005;Lundqvist et al, 2020), auditory (de Pesters et al, 2016;Potes et al, 2014), and somatosensory stimuli (Fontolan et al, 2014), and during motor responses (Crone et al, 1998;de Pesters et al, 2016;Jiang et al, 2020;Miller et al, 2007) and task/cognitive processing (Asher et al, 2007;Hwang & Andersen, 2011). Several M/EEG studies observed a negative relationship between low-frequency power decrease and, what is reported as, narrowband gamma increase (Bauer et al, 2006;Kloosterman et al, 2019;van Ede et al, 2014;Wyart & Tallon-Baudry, 2009); though it remains unclear whether this high-frequency signal reflects genuine oscillatory activity or broadband power.…”
Section: Simultaneous Relationship Between Alpha Oscillations and Excmentioning
confidence: 98%
“…Additionally, they are also consistent with numerous studies suggesting a negative relationship between low-frequency power, including the alpha band, and high-frequency power, including BHA, during sensory, motor and task processing. Specifically, increased high-frequency power co-occured with decreased low-frequency power after the presentation of visual (Lachaux et al, 2005;Martin et al, 2019;Nir et al, 2007Nir et al, , 2017Rodriguez et al, 2004;Fisch et al, 2009;Miller et al, 2014;Podvalny et al, 2015;Fries et al, 2001;Scheeringa et al, 2011;Hwang & Andersen, 2011;Rickert et al, 2005;Lundqvist et al, 2020), auditory (de Pesters et al, 2016;Potes et al, 2014), and somatosensory stimuli (Fontolan et al, 2014), and during motor responses (Crone et al, 1998;de Pesters et al, 2016;Jiang et al, 2020;Miller et al, 2007) and task/cognitive processing (Asher et al, 2007;Hwang & Andersen, 2011). Several M/EEG studies observed a negative relationship between low-frequency power decrease and, what is reported as, narrowband gamma increase (Bauer et al, 2006;Kloosterman et al, 2019;van Ede et al, 2014;Wyart & Tallon-Baudry, 2009); though it remains unclear whether this high-frequency signal reflects genuine oscillatory activity or broadband power.…”
Section: Simultaneous Relationship Between Alpha Oscillations and Excmentioning
confidence: 98%
“…Therefore, any attenuation of the high-frequency band in EEG can be considered as removal of EMG artifacts. Also, μ desynchronization in EEG and ECoG signals is a well-known modulation underlying motor behavior (Pfurtscheller and Da Silva, 1999 ; Miller et al, 2007 ; Schalk et al, 2007 ; Jiang et al, 2020 ). Therefore, these two bands are used jointly as an indicator that our approach is effective at removing EMG artifacts while preserving the brain physiological features underlying human movement.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, high-γ band of brain activities was demonstrated to synchronize to movement (Flint et al, 2014(Flint et al, , 2016Wang et al, 2017;McCrimmon et al, 2018;Branco et al, 2019) while µ band was desynchronized (Miller et al, 2007a;Schalk et al, 2007;Jiang et al, 2020). To evaluate if these electrophysiological features and information content underlying movement were retained after ERASE, the signal-to-noise ratio (SNR) between movement and idle was calculated for electrodes expected to be related to thumb movements, including C3, C5, C1, FCC5h, FCC3h, CCP5h, and CCP3h for subjects with left-sided hemicraniectomy, or C4, C2, C6, FCC6h, FCC4h, CCP4h, and CCP6h for those with right-sided hemicraniectomy.…”
Section: Signal-to-noise Ratio (Snr) Calculationmentioning
confidence: 95%